Paulo Freire and the Argentine social workers. The Early Intellectual Reception of the Brazilian Pedagogue in the Social Work’s Professional Reviews, 1969 – 1973 (Palimpsesto, 2021)
This work is an advance of the research process on the intellectual reception of the written work of Paulo Freire in the professional reviews of the Argentine Social Work between the years 1969 and 1973. The vital trajectory of the Brazilian pedagogue Paulo Freire is an essential data to the conditions of production and dissemination of his ideas and even of their reception in the field of Argentine social work. The 1969 Social Service Congress in Santiago de Chile was the high point of the relationship between Freire's educational ideas in the professional field and the radicalized politics of the organizations of the Latin America’s new left. The trips of the Brazilian intellectual to Argentina, and the exchanges through international seminars and congresses were the vehicles for the circulation of pedagogical ideas, in which the categories of 'conscientization', 'praxis' and 'liberation' are introduced in a mixture of Catholic and populist readings and readers in the process of political radicalization. We investigate the dissemination of Freirean thought in professional reviews Hoy en el Servicio Social and Selecciones del Servicio Social, identify the intellectuals who read the work of the Brazilian pedagogue, and analyze the appropriations in a web of meaning. This work stops on the instrumentalization of Freirean ideas in the intellectual debate of Social Work in professional reviews to contribute to the knowledge of the history of the discipline in our country.
Keywords: Social Work; Freire; New Left; Intellectuals